2009
DOI: 10.3126/jfl.v5i1.1981
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Concept of Forest-Based Enterprise Development in Nepal: Towards a Pro-Poor Approach

Abstract: This paper demonstrates that community forests have high potential to make a significant contribution to rural income and employment through non-timber forest products enterprises particularly to the poor. The paper highlights a practical experience of the pro-poor entrepreneurship approach, its process, steps and outcomes through examination of a recently-developed enterprise in Jiri, Dolakha district of the central hills region of Nepal. The paper concludes that there are five key aspects which need addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Based on other studies (e.g. Acharya, 2005;Pokharel et al, 2006 andPun andShrestha, 2008), enterprises operated by the community are generating significant income at the community level. Acharya (2005) reported that there was 11% increment in the household level income from CBFE of the Dolakha district.…”
Section: Income From Enterprisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on other studies (e.g. Acharya, 2005;Pokharel et al, 2006 andPun andShrestha, 2008), enterprises operated by the community are generating significant income at the community level. Acharya (2005) reported that there was 11% increment in the household level income from CBFE of the Dolakha district.…”
Section: Income From Enterprisesmentioning
confidence: 99%
“…In this study, the mean income from the NTFPs based enterprises was found lower than other enterprises. Technology development for NTFPs collection and processing is not adequate (Pokharel et al, 2006).…”
Section: Income From Enterprisesmentioning
confidence: 99%
“…The most recent projects have supported about 100 enterprises over a 3-year period in the early 2010s (Kunwar et al 2009;Rai et al 2016). Working in districts such as Dolakha, the Nepal Swiss Community Forestry Project adopted a pro-poor entrepreneurship approach (Pokharel et al 2006). CARE's initiatives in the late 2000s in the Churia's Sarlahi and Mahottari district for improving livelihood security of poor and vulnerable people through watershed management and social equity focused on NTFP/MAPs enterprises (Khanal and Bhujei 2008).…”
Section: Emergence and Growth Of Communitymanaged Forest Enterprisesmentioning
confidence: 99%
“…Thus, community forestry has shifted its main focus from securing subsistence requirements of communities towards maximization of profits by satisfying demands of the market (Pokharel et al 2006). In recent years, there has been a growing trend of involvement of CFUGs in commercial activities.…”
Section: Towards Commercilizationmentioning
confidence: 99%
“…The burden of development has transferred to local level under the contemporary developmental paradigm. Schools, health posts, road, irrigations, and community infrastructure have been designated as local responsibility, needing more financial resources (Pokharel et al, 2006;Springate-Baginski and Blaikie 2003).…”
Section: Commercial Alliances and Cfug Fundsmentioning
confidence: 99%